Indian hedgehog signaling is required for proper formation, maintenance and migration of Xenopus neural crest - Agüero, Tristán Horacio (2012)
Neural crest induction is the result of the combined action at the neural plate border of FGF, BMP, and Wnt signals from the neural plate, mesoderm and nonneural ectoderm. In this work we show that the expression of Indian hedgehog (Ihh, formerly named Banded hedgehog) and members of the Hedgehog pathway occurs at the prospective neural fold, in the premigratory and migratory neural crest. We performed a functional analysis that revealed the requirement of Ihh signaling in neural crest development. During the early steps of neural crest induction loss of function experiments with antisense morpholino or locally grafted cyclopamine-loaded beads suppressed the expression of early neural crest markers concomitant with the increase in neural and epidermal markers. We showed that changes in Ihh activity produced no alterations in either cell proliferation or apoptosis, suggesting that this signal involves cell fate decisions. A temporal analysis showed that Hedgehog is continuously required not only in the early and late specification but also during the migration of the neural crest. We also established that the mesodermal source of Ihh is important to maintain specification and also to support the migratory process. By a combination of embryological and molecular approaches our results demonstrated that Ihh signaling drives in the migration of neural crest cells by autocrine or paracrine mechanisms. Finally, the abrogation of Ihh signaling strongly affected only the formation of cartilages derived from the neural crest, while no effects were observed on melanocytes. Taken together, our results provide insights into the role of the Ihh cell signaling pathway during the early steps of neural crest development. © 2012 Elsevier Inc.